2020
DOI: 10.1021/acsanm.0c00630
|View full text |Cite
|
Sign up to set email alerts
|

Chrysin-Anchored Silver and Gold Nanoparticle-Reduced Graphene Oxide Composites for Breast Cancer Therapy

Abstract: Natural polyphenol assisted fabrication of nanohybrids with improved stability and bioactivity have gained considerable interest in material science. In this study, the anticancer flavone chrysin (5,7-dihydroxyflavone ChR) was employed to fabricate silver (AgNPs) and gold nanoparticles (AuNPs) hybridized reduced graphene oxide (rGO) nanocomposites (ChR@Ag-rGONCs and ChR@Au-rGONCs) with long-term stabilities. Prepared nanocomposites (NCs) were characterized using high-throughput analyses. The hydroxyl (O–H) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(16 citation statements)
references
References 69 publications
1
15
0
Order By: Relevance
“…Gnanasakar et al demonstrated a significant cytotoxic effect of prepared nanocomposites against MDA-MB-468 and MDA-MB-231 cell lines compared to normal cells by inducing apoptosis. The overall result of this study suggests that the prepared metal-rGO nanocomposites functionalized with 5,7-dihydroxy flavones have a bright future for cancer chemotherapeutic purposes [8].…”
Section: Introductionmentioning
confidence: 75%
“…Gnanasakar et al demonstrated a significant cytotoxic effect of prepared nanocomposites against MDA-MB-468 and MDA-MB-231 cell lines compared to normal cells by inducing apoptosis. The overall result of this study suggests that the prepared metal-rGO nanocomposites functionalized with 5,7-dihydroxy flavones have a bright future for cancer chemotherapeutic purposes [8].…”
Section: Introductionmentioning
confidence: 75%
“…For a step toward the improvement of stability and bioactivity, natural polyphenols have been utilized in combination with the G‐based nanocomposites. Sivaperumal and co‐workers 137 have described the preparation of silver and gold nanoparticles hybridized with reduced GO nanocomposites and deploying the anticancer flavone, chrysin with improved stability, bioactivity, and biocompatibility. These nanohybrids had enhanced cytotoxic effects against breast carcinoma cell lines with low toxicity to the normal cells; the formation of ROS discharged by the co‐existing metal ions on the reduced GO promoted apoptosis 137 .…”
Section: Important Challenges and Future Perspectivesmentioning
confidence: 99%
“…These nanohybrids had enhanced cytotoxic effects against breast carcinoma cell lines with low toxicity to the normal cells; the formation of ROS discharged by the co-existing metal ions on the reduced GO promoted apoptosis. 137 Some natural polyphenolic flavonoids with anticancer effects (e.g., quercetin) have been utilized to generate G-and GO-based nanosystems with controlled drug delivery; high cytotoxicity toward cancerous cells and targeted drug delivery properties could be attained by these nanosystems. 138 Because of the serious adverse effects and non-targeting disadvantages of chemotherapy tactics, researchers have instigated extensive investigations into innovative nanostructures that have led to the design of a wide range of effective nanosystems for the treatment of cancers.…”
Section: Important Challenges and Future Perspectivesmentioning
confidence: 99%
“…Fabrication of chrysin-attached to silver and gold nanoparticles crossbred reduced graphene oxide nanocomposites led to augmentation of the generation of ROS-induced apoptosis in breast cancer [ 91 ]. Chrysin loaded PCL-PEG-PCL had greater antitumor impact on gene expression of BRCA1, FTO, and hTERT in comparison to free chrysin [ 92 ].…”
Section: Cellular and Molecular Mechanisms Involved In The Therapeutic Effects Of Chrysinmentioning
confidence: 99%